Reasons, Holism And Virtue Theory. (19th March 2013) - Jordan, Andrew
Abstract : Some particularists have argued that even virtue properties can exhibit a form of holism or context variance, e.g. sometimes an act is worse for being kind, say. But, on a common conception of virtuous acts, one derived from Aristotle, claims of virtue holism will be shown to be false. I argue, perhaps surprisingly, that on this conception the virtuousness of an act is not a reason to do it, and hence this conception of virtuous acts presents no challenge to particularist claims about the context variance of reasons. Still, I argue that the virtues nevertheless have important implications for our understanding of the particularism debate. Specifically, we can accept the particularist claim that reasons do not need to be principled in order to have the normative status that they do have, while still maintaining that sound moral thought and judgement has a principled structure understood in terms of the virtues.